Optimal placement of unified power flow controller using differential search algorithm. (2nd September 2019) - Banerjee, Dhiman; Bhattacharya, Sriparna; Roy, Provas Kumar
Optimal power flow (OPF) problem plays a crucial role to run an economically efficient and well-planned power system. It is a challenging task for the power system researchers to cope with the ever-increasing load-demand while getting the minimum system loss. The development of flexible ac transmission system (FACTS) has added a new dimension both to the system operation and research. Unified power flow controller (UPFC) is the most reliable FACTS controller, which can provide both series and shunt compensation. As a matter of fact, UPFC can reliably control the different power system parameters. In this article, UPFC is incorporated into the modified IEEE 5-bus and modified IEEE 30-bus test system. Differential search algorithm (DSA) is proposed and implemented to run the OPF with and without UPFC and the results are listed, analysed and compared with the same that is obtained by genetic algorithm (GA) and BAT search algorithm.